2019
DOI: 10.1177/1460458219879340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the factors that influence cloud technology adoption—comparative case analysis of health and non-health sectors: A systematic review

Abstract: Cloud technology has brought great benefits to the health industry, including enabling improvement in the quality of services. The objective of this review study is to investigate the reported factors affecting the adoption of cloud in the health sector by comparing studies in the health and non-health sectors. This article is a systematized review of studies conducted in 2018. From 541 articles, 47 final articles were selected and classified into two categories: health and non-health studies; conclusions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Specifically, the results revealed that perceived ease of use has a significant positive effect on the intention to use cloud computing (H1), perceived usefulness has a significant positive effect on the intention to use cloud computing (H2), reliability has a significant positive impact on the users' intention to opt for cloud computing services (H3), and responsiveness has a significant positive impact on the users' intention to opt for cloud computing tools (H4). These findings are in line with the TAM model [8], [17], [18], [23].…”
Section: Hypothesis Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, the results revealed that perceived ease of use has a significant positive effect on the intention to use cloud computing (H1), perceived usefulness has a significant positive effect on the intention to use cloud computing (H2), reliability has a significant positive impact on the users' intention to opt for cloud computing services (H3), and responsiveness has a significant positive impact on the users' intention to opt for cloud computing tools (H4). These findings are in line with the TAM model [8], [17], [18], [23].…”
Section: Hypothesis Testingsupporting
confidence: 89%
“…In the health sector, Sadoughi, Ali, and Erfannia [17] investigated and compared the factors that affect the adoption of cloud computing in health and non-health sectors. From a review of 541 articles, the authors found that the factors that mostly affect cloud computing implementation are pigeon-holed as the factors were related to technological, organizational, environmental, and individual aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In total, five studies examined this topic [8,10,[24][25][26][27][28][29] as well as identified a number of blogs, opinion papers, communications and one ahead-of-print publication [7,8,[30][31][32][33][34][35][36][37][38][39][40]. At last, out of all studies retained for review, two of them aimed to examine learning transfer [41,42].…”
Section: Phase 1 Results: Overview Of the Examined Literaturementioning
confidence: 99%
“…Achieving a proper balance between security and access is an important success and vital factor in healthcare management systems (Ben-Zion et al , 2014). Trusting the vendor is also a significant factor in adopting cloud computing (Alotaibi, 2014); especially, security and privacy are critical in healthcare among hospitals, which are important and correct issues due to the sensitivity of information stored in the cloud (Hyson, 2014; Sadoughi et al , 2020).…”
Section: Resultsmentioning
confidence: 99%